PENGARUH PERILAKU HIDUP BERSIH DAN SEHAT TATANAN RUMAH TANGGA TERHADAP PENCEGAHAN COVID-19 PADA WARGA RT 03 RW 01 KECAMATAN BABAKAN CIPARAY KOTA BANDUNG - Gustini, Farida; Merlianawati, Indah (Jurnal Infokes, 2021)
Aims to determine the effect of clean and healthy household behavior on the prevention of COVID-19 in residents of RT 03 RW 01 Babakan Ciparay Sub-District, Bandung City. The research method used by the author is quantitative research with a descriptive approach. Data collection techniques used are observation, interviews, literature study, questionnaires. The research sample used population research on 80 residents of Rt 03 Rw 01 Babakan Ciparay Sub-District, Bandung City From the results of the study, it was found that for the residents of RT 03 RW 01, Clean and Healthy Living Behavior The household structure was good (88%) as well as the prevention of COVID-19 (87%) and had a correlation level between variable X and variable Y of 0.748 means that they have a strong relationship. The magnitude of the influence of X on Y is equal to 55.9%, so that there are still other variables that influence Y, namely 44.1%. The problems that were found from the research conducted were (1) The low level of maintaining distance when in a crowd. (2) Lack of awareness in wearing masks when in the environment around the house. (3) Some residents when coughing cover their mouths with their palms and didn’t wash their hands immediately. The author provides suggestions on these problems, namely (1) Increase in maintaining distance when in a crowd in efforts to prevent COVID-19. (2) Wearing a mask even in the environment around the house. (3) Understand hygiene and healthy living habits in cough ethics in order to prevent the spread of COVID-19.